Use of chemical and biological products in modern shrimp farming in Northern Tamil Nadu, India - Deboral Vimala, D.; Ravisankar, T.; Gopal, C.; Ravichandran, P. (Indian Journal of Fisheries, 2015)
Chemical and biological (CB) products are extensively used in present day aquaculture. Though some of these products help to improve the quantity and quality of aquaculture production, their indiscriminate use could lead to deleterious effects on the production system. To assess the use of commercial CB products in shrimp aquaculture, data were collected from 103 shrimp farmers in two districts in northern Tamil Nadu, viz., Kanchipuram and Tiruvallur. Based on the study, it was found that many manufacturers and retailers of these products provided farmers with information and relevant instructions for their safe and effective use. Availability of 110 different CB products in the market was documented. Farmers from Kanchipuram and Tiruvallur districts used 27 and 51 different types of CB products respectively and among the two districts, the farmers in Tiruvallur District used larger number of CB products. On an average 5 to 17 CB products were used by each farmer in the study area. Disinfectants, soil and water treatment formulations/probiotics, feed probiotics, feed additives and immunostimulants were the most commonly used CB products. Neither the age of the farmer nor their experience in farming had influence on selection, use and continuance of CB products. The deciding factor on the use of CB products was found to be technician’s advice. The main rationale for use of a CB product was for improvement of soil quality. The present investigation identified the market profile of CB products, usage pattern and the expenditure incurred in their use. Notably none of the farmers in the study area used antibiotics.